Diagnostic Utility of Total IgE in Foods, Inhalant, and Multiple Allergies in Saudi Arabia. (25th May 2016) - Al-Mughales, Jamil A.
Abstract : Objective. To assess the diagnostic significance of total IgE in foods, inhalant, and multiple allergies. Methods. Retrospective review of the laboratory records of patients who presented with clinical suspicion of food or inhalant allergy between January 2013 and December 2014. Total IgE level was defined as positive for a value >195 kU/L; and diagnosis was confirmed by the detection of specific IgE (golden standard) for at least one food or inhalant allergen and at least two allergens in multiple allergies. Results. A total of 1893 (male ratio = 0.68, mean age = 39.0 ± 19.2 years) patients were included. Total IgE had comparable sensitivity (55.8% versus 59.6%) and specificity (83.9% versus 84.4%) in food versus inhalant allergy, respectively, but a superior PPV in inhalant allergy (79.1% versus 54.4%). ROC curve analysis showed a better diagnostic value in inhalant allergies (AUC = 0.817 (95% CI = 0.796–0.837) versus 0.770 (95% CI = 0.707–0.833)). In multiple allergies, total IgE had a relatively good sensitivity (78.6%), while negative IgE testing (<195 kU/L) predicted the absence of multiple allergies with 91.5% certitude. Conclusion. Total IgE assay is not efficient as a diagnostic test for foods, inhalant, or multiple allergies. The best strategy should refer to specific IgE testing guided by a comprehensive atopic history.